E-Viral Marketing Influence and Underlying Marketing Strategies: Social Relationship Variables - Goyal, Aparna P. (Indian Journal of Computer Science, 2018)
This study focused on five social relationship variables: social capital, tie strength, homophile, trust, and interpersonal influence that are all related to viral word of mouth behavior in social networking sites. Its aim was to provide aÂ theoretical understanding of use of social networking sites by consumers as a vehicle for viral word of mouth. Specifically, the current study attempted to empirically examine potential roles of social factors in viral word of mouth. At the same time, findings from this research can provide marketers with valuable information to establish their long-term relationships with consumers in social networking sites and use of beneficial viral word of mouth to promote selected brands.The research of consumers is influenced by viral word of mouth and canbe used to discover different conceivable marketing outcomes and makes it simple to take advantage of them effectively. It discovers whether products or services is compelling for the consumers or not.The research explored the factors influencingviral word of mouth via social networking services on consumers’ purchase intention. Further, it helps discuss weather social capital has positive influence for viral word of mouth via social networking services on consumers’ purchase intention, whether the stronger the tie strength has positive influence for viral word of mouth via social networking services on consumers’ purchase intention and discusses whether the more homophilious contacts have positive influence for viral word of mouth via social networking services on consumers’ purchase intention.